Assistance and Banner Provision as a Strategy to Enhance Marketing Performance of Teng-Teng MSME Products - Sinar; Muhammad Azhar Nur; Nurwahida; Hardiyanti Ridwan; Diyah Fadillah (www.amertainstitute.com, 2026)
This community service activity aims to enhance the marketing performance of micro, small, and medium enterprises (MSMEs) through structured assistance and the provision of promotional banners. The program focused on Teng-Teng and banana chip MSMEs located in Pasir Putih Village, Sinjai Borong District, which face common challenges related to limited promotion, branding, and market visibility. The assistance was implemented through direct involvement in the production process and the development of promotional media in the form of banners designed to represent product identity and attract consumer attention. The activities were conducted in three stages: initial socialization with local stakeholders, production assistance, and promotional support through banner installation. The assistance sessions took place on February 20 and March 3, 2023, followed by banner installation on March 20, 2023. The results indicate that the provision of banners as promotional media improved product visibility and strengthened brand recognition among the local community. Moreover, the assistance process increased MSME actors’ awareness of the importance of marketing strategies and product presentation in supporting business sustainability. This activity demonstrates that simple promotional interventions combined with mentoring can contribute positively to MSME marketing development, particularly in rural areas with limited access to formal marketing channels. The findings suggest that assistance-based promotional strategies can serve as an effective approach to support MSME competitiveness and income improvement.